The People of the Philippines letter from the Secretary of War, transmitting an article on the people of the Philippines (Document / 56th Congress, 2nd Session, Senate, 1901)
The People of the Philippines, compiled in the Division of Insular Affairs from standard works and the records of the Department, supplemented by the personal experience of returning officers.